TNF-Α may mediate inflammasome activation in the absence of bacterial infection in more than one way. - Susana Álvarez (Public Library of Science (PLoS), 2013)
Members of the mammalian nucleotide binding domain, leucine-rich repeat (LRR)-containing receptor family of proteins are key modulators of innate immunity regulating inflammation. To date, microbial pathogen-associated molecules and toxins have been identified as key triggers of activation of inflammasomes. However, recently, environmental, and neurodegenerative stimuli have been identified that lead to IL-1β release by means of inflammasomes. IL-1β plays a crucial role during brain inflammation, and caspase-1 appears to be a key modulator of IL-1β bioactivity and the consequent transcriptional regulation of gene expression within the brain during inflammation. We show here that exposure of a human neuroblastoma cell line (SK-N-MC cells) to TNF-α promotes ROS-mediated caspase-1 activation and IL-1β secretion. The involvement of NF-κB in the regulation of IL-1β synthesis is investigated through specific inhibition of this transcription factor. The effect of TNF-α was abolished in the presence of ROS inhibitors as NAC, or DPI. Remarkably, SK-N-MC cells do not respond to ATP stimulation in spite of P2X7R expression. These results provide a mechanism by which danger signals and particulate matter mediate inflammation via the inflammasome in the absence of microbial infection.